(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
In today’s digital era, the protection of sensitive information has become a crucial aspect for state bodies and their databases. With the increased reliance on technology, information security risks have also escalated, demanding comprehensive measures to safeguard these databases from unauthorized access, data breaches, and other potential threats. This article explores various methods and means employed by state bodies to protect their database services from information security risks.